THE EFFECT OF FINANCIAL PERFORMANCE ON CORPORATE VALUE WITH DIVIDEND POLICY AS MODERATING VARIABLES IN MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE - Sari, Melati Puspita (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to determine and analyse the Effect of Financial Performance on Firm Value with Dividend Policy as a Moderating Variable in Manufacturing Companies on the Indonesia Stock Exchange. The type of this research is causal associative. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2008 to 2017. The sample selection is done by purposive sampling technique, so the number of samples used is 200 sample data. The data analysis method uses path diagram and Goodness of Fit The results of the study show that profitability, liquidity, leverage and activity ratios have a positive and significant effect on firm value while manufacturing companies listed on the Indonesia stock exchange. Dividend policy is not able to moderate the relationship between profitability, liquidity, leverage and the ratio of activity to firm value at the company manufacturers listed on the Indonesia stock exchange.